ESTIMADOR DE KERNEL PARA DETERMINAR ZONAS DE RISCO DE INCÊNDIO NO ESTADO DE MATO GROSSO DO SUL - FRANÇA, Hellen Lorraine Rocha; SILVA, Jhony Ferry Mendonça; ROSSET, Jean Sérgio; CASTILHO, Selene Cristina de Pierri; MARRA, Leandro Marciano (ANAIS DO ENIC, 2020)
-